Management of Health Facilities Medical Waste on Lombok Island, West Nusa Tenggara Province - Yusril Akbar Ibrahim (Rifa'Institute, 2022)
Background: one of the effects or impacts arising from the implementation of health service activities is the emergence of medical waste. Medical waste generated can be at high risk of causing negative side effects for health if not handled properly. In Indonesia itself, it has implemented regulations related to medical waste management in health facilities listed in the region-based medical waste management program. Lombok Island, West Nusa Tenggara Province is one of the target areas in this program, however, there are still some shortcomings in the implementation of medical waste management and disposal so it still poses a high health risk. Method: The method used is qualitative, with the collection of literature sources that meet the criteria for analysis. Objective: To determine developments in the management and disposal of medical waste on the island of Lombok, West Nusa Tenggara. Results: From the results of 3 literature reviews, it is shown that not one hundred percent of the management and disposal of medical waste in health facilities on the island of Lombok has been carried out in accordance with government recommendations. Regarding the separation of medical and non-medical waste, sharps waste and general waste are still not appropriate. Disposal of medical waste is not in accordance with the specified quality standard threshold. Conclusion: Medical waste management at Lombok Island Health Facilities needs to get further attention related to sorting to proper management and disposal.